التحضير الدوائي عند الأطفال الخاضعين للتنظير الهضمي (Latakia University Journal -Medical Sciences Series, 2019)
إن التطبيق الوريدي للميدازولام مع أو بدون المورفينات narcotics يستخدم بصورة شائعة في أثناء التنظير الهضمي العلوي عند الأطفال لتأمين التركين الواعي، ومع ذلك فإن الأطفال يعانون من القلق والخوف قبل تطبيق هذه المواد وريديا لهم ،وخاصة في زمن فصلهم عن أهلهم، أو في زمن فتح الوريد. وبالتالي فإن وسائل أخرى كالتطبيق عبر الأنف للميدازولام قد يؤمن طريقة غير باضعة  noninvasiveوفعالة لتركين الطفل الذي سيخضع للتنظير . إن التركيز الدوائي بتطبيق الميدازولام عبر الأنف للأطفال الذين سيخضعون للتنظير الهضمي فعّال بصورة واضحة في تقليل العلامات السلوكية السلبيّة خاصة في مرحلة فصل الطفل عن أهله. وسيساهم كثيرا في تسهيل إجراء المراحل اللاحقة (فتح الوريد ، EGD ) .إن هذا التأثير الإيجابي يؤثر فيه الإحساس المخرش الناجم عن تطبيق الدواء عبر الأنف. Intravenous midazolam and opioids are used to produce conscious sedation in children undergoing esophagogastroduodenoscopy (EGD). However, children may experience significant fear and anxiety before receiving these medications, especially during separation from parents and during venipuncture. Intranasal administration of midazolam represents a noninvasive method of sedating children before anxiety-producing events. The objective of this study is to determine whether premedication with intranasal midazolam reduces stress and anxiety of separation from parents and of undergoing venipuncture, while maintaining adequate sedation during EGD. Premedication with intranasal midazolam is effective in reducing negative behavior during separation from parents, while maintaining sedation during the endoscopic procedure. However, the benefits of intranasal administration may be affected by irritation and discomfort caused by intranasal drug administration.